Enhanced Recovery Achieving the Aims of Head and Neck Cancer Surveillance: A Traffic Light System. (23rd August 2013) - Lee, Alexandra M.; Oakley, Richard J.; Joshi, Anil; Lyons, Andrew; Simo, Ricard; Urbano, Teresa G.
Abstract : Objectives: Post‐treatment head and neck cancer surveillance (PTHNCS) shows inconsistency in the duration of surveillance and frequency between reviews; its rationale is controversial although generally accepted. We pilot a PTHNCS that uses the principles of enhanced recovery and implements the recommendations of the Head and Neck Cancer multi‐disciplinary 2011 guidelines (HNCMDG). Methods: Retrospective review. The recommendations of the HNCMDG 2011 were used to generate a 15 visit, 5 year PTHNCS protocol. A traffic light analogy explains its rationale and reinforces the positive implications associated with progression to patients. A patient appointment/information card has been developed to outline the five year surveillance schedule and highlight red flag symptoms that suggest recurrence and require early review. The follow up of all patients who completed chemoradiation for HNC in the first half of 2011 was compared. Results: 47 patients received treatment: 21 patients on PTHNCS protocol, 20 (95%) attended the minimum number of visits, 4 requested additional reviews (one for a synchronous primary), none lost to follow up, 1 died. 26 patients followed at the clinicians discretion, 11 (42%) attended the minimum number of appointments, 2 did not, 1 never saw the surgical team, 1 lost to follow up, 11 died. Conclusions: Empowering patients to participate in their follow up while educating them as to symptoms that require earlier review allows an increase in interval follow up of asymptomatic patients. Symptomatic patients initiate an earlier review. Fewer patients are lost to follow up.